The story of chocolate - Daynes, Katie; Larkum, Adam Kelly, Alison (Usborne London, 2006)
The fascinating history of chocolate, from its origins in the rainforests of Central America to shops and factories everywhere. Written as part of the Usborne Young Reading Programme, designed for children just beginning to read.